2011
DOI: 10.1155/2011/165214
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Resistance to EGFR TKIs and Development of a New Generation of Drugs in Non‐Small‐Cell Lung Cancer

Abstract: Gefitinib and erlotinib, which are epidermal growth factor receptor- (EGFR-) specific tyrosine kinase inhibitors (TKIs), are widely used as molecularly targeted drugs for non-small-cell lung cancer (NSCLC). Currently, the search for EGFR gene mutations is becoming essential for the treatment of NSCLC since these have been identified as predictive factors for drug sensitivity. On the other hand, in almost all patients responsive to EGFR-TKIs, acquired resistance is a major clinical problem. Mechanisms of acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(103 citation statements)
references
References 54 publications
0
101
0
2
Order By: Relevance
“…Previous studies have demonstrated the benefits of afatinib on patient OS using pooled data from the LUX-lung 3 and 6 clinical trials (11,12,18). Afatinib is hypothetically more effective at inhibiting EGFR signaling than reversible TKIs, due it forming stable covalent bonds and irreversibly inhibiting ATP from binding to the tyrosine kinase domain of EGFR (19); however, no randomized clinical trial or meta-analysis has demonstrated that afatinib is superior to erlotinib or gefitinib regarding OS. Irreversible TKIs have been reported to significantly improve the OS time of patients with exon 19 deletions (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the benefits of afatinib on patient OS using pooled data from the LUX-lung 3 and 6 clinical trials (11,12,18). Afatinib is hypothetically more effective at inhibiting EGFR signaling than reversible TKIs, due it forming stable covalent bonds and irreversibly inhibiting ATP from binding to the tyrosine kinase domain of EGFR (19); however, no randomized clinical trial or meta-analysis has demonstrated that afatinib is superior to erlotinib or gefitinib regarding OS. Irreversible TKIs have been reported to significantly improve the OS time of patients with exon 19 deletions (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…These agents effectively inhibit EGFR activity by irreversible binding to EGFR. Afatinib (BIBW2992) and dacomitinib (PF299804) are representative second-generation irreversible EGFR TKIs currently undergoing clinical trial and have shown promising antitumor activity in NSCLC (6,7). Because these agents have been reported to exhibit antitumor activity in preclinical studies using NSCLC cells harboring the EGFR T790M, they are expected to be standard therapeutic options for patients with EGFR T790M (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…A small molecule Met inhibitor combined with an EGFR TKI has proven to be a reasonable strategy to overcome erlotinib-resistant T790M NSCLC (Li et al, 2008). Combining an insulin-like growth factor inhibitor with erlotinib to reverse resistance to erlotinib is also under investigation (Tang et al, 2008;Kosaka et al, 2011). However, most of these treatments are not clinically available.…”
Section: Discussionmentioning
confidence: 99%